INTERNALIZATION OF ASWAJA VALUE THROUGH CHARACTER EDUCATION BASED ON CHILDREN'S LITERATURE - Fauziah, Ikfina Hesti (TAWASUT, 2024)
AbstractForming a nation with character must start at an early age. One of the efforts that can be used in building children's character is through children's literature-based learning. Literary works become a comprehensive medium for character education. Through literary works, characters and roles are played, the environment that becomes the background is spread out, and noble values as literary mandates are taught. Therefore, the use of literary works as a medium for character building through education in schools needs to be brought back to the surface in various ways that involve various parties. This research is a descriptive literature research. The results of this study indicate that the internalization of Aswaja characters such as 1) religious character values; 2) democratic character values; 3) the value of the character of love for the homeland; 4) fair character values; 5) the value of disciplined character; 6) independent character values; and 7) the value of the character of tolerance, which can be applied through children's literature, especially in literary works in the form of stories using the storytelling method. Storytelling is very effective in inculcating children's character because in children's literature that is told, children can imitate characters in stories with ideal norms and take the attitudes and behavior of characters as examples. Keywords: Character, Aswaja, Children's Literature